ESTIMATING ECONOMIC LOSSES FROM SINABANG EARTHQUAKE USING AN EMPIRICAL APPROACH - Teguh Rahayu; Tavi Supriana; Adisti Tristania Firmansyah (Universitas Methodist Indonesia, 2020)
The empirical approach is a potential candidate along with other engineering-based loss models within the Prompt Assessment of Global Earthquakes for Response (PAGER) system for rapid social and economic loss estimation. In this study, we focused to evaluate the Sinabang earthquake on 7 January 2020 with Magnitude 6.3. The result of this study shown the green alert for shaking related fatalities and economic losses in 65 % from the estimated fatalities and losses in Sinabang.